Desarrollo de una propuesta para un microseguro de robo, incendios y líneas aliadas, dirigidas a pequeños negocios para la compañía Seguros Oriente S.A., en la ciudad de Quito como alternativa para la ampliación de la protección social en caso de siniestros - Cueva Encalada, Ana María (2015)
One problem that affects small businesses, is the impact that occurs in cash flows due to unforeseen events whose occurrence prevents an optimal level of revenues to continue, causing a negative effect on profitability and the Lifestyle's owner. It is for this reason, this proposal focuses on the creation of a micro insurance of fire, theft and allied lines easily accessible and inexpensive to provide a backup in case of a sudden and unexpected as theft event occurs, fire, earthquakes and other natural disasters that cause material or economic loss. The purpose of this service is to support small business owners in the Quito's city, by protecting the investment you made when purchasing your business if a loss occurs, so that in this way, the impact suffering is smaller and can resume their business activities without its assets is impaired, allowing them to improve their quality of life and generating a positive effect on society.